(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Medard Boss (1903-1990), the founder of therapeutic daseinanalysis (Daseinsanalyse), introduced into existential analysis Carlos Alberto Seguín’s notion of the therapeutic eros. This, the effective element of daseinanalytic therapy, is based on Augustine’s classic expression "love, do what you will." The daseinanalyst’s non-interventional love is a gift directed at the Dasein, not the person, of the analysand. It is offered in the spirit of a way-making caring for the other.